Genomic mapping with I-Ceu I, an intron-encoded endonuclease specific for genes for ribosomal RNA, in Salmonella spp., Escherichia coli, and other bacteria. - Liu, S L (1993)
Construction of physical maps of genomes by pulsed-field gel electrophoresis requires enzymes which cut the genome into an analyzable number of fragments; most produce too many fragments. The enzyme I-Ceu I, encoded by a mobile intron in the chloroplast 23S ribosomal RNA (rrl) gene of Chlamydomonas eugametos, cuts a 26-bp site in the rrl gene. This enzyme digests DNA of Salmonella typhimurium at seven sites, each corresponding to one of the rrl genes of the rrn operons, but at no other site. These seven fragments were located on the previously determined Xba I physical map, and the I-Ceu I sites, and thus the rrn genes of S. typhimurium, were mapped on the 4800-kb chromosome. Escherichia coli K-12 also yields seven fragments of sizes similar to those of S. typhimurium, indicating conservation of rrn genes and their location, and a chromosome size of 4600 kb. The sizes of the E. coli fragments are close to the size predicted from restriction maps and nucleotide sequence. The I-Ceu I maps of Salmonella enteritidis, Salmonella paratyphi A, B, C, and Salmonella typhi were deduced after digesting genomic DNA and I-Ceu I and probing with DNA of S. typhimurium; the data indicated strong conservation of rrn gene number and position and genome sizes up to 4950 kb. Digestion of DNA of other bacteria (species of Haemophilus, Neisseria, Proteus, and Pasteurella) suggested that only rrn genes are cut in all these species. I-Ceu I digestion followed by pulsed-field gel electrophoresis is a powerful tool for determining genome structure and evolution.